Relationship Between Profitability, Investment Decisions On Firm Value: A Study Of Listed Banks In Indonesia - Sa’diyah, Chalimatuz (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2021)
The purpose of this study is to determine the effect of profitability, capital structure, and investment decisions on firm value in the property, real estate and building construction sectors listed on the Indonesia Stock Exchange for the 2015-2019 period. The population in this study were 83 companies. The sampling technique in this study was purposive sampling and produced a sample of 30 companies. The data analysis technique in this study uses multiple linear regression, while the analysis tool used is SPSS 25. This research hypothesis states that profitability has a positive and significant effect on firm value, capital structure has a positive and significant effect on firm value, investment decisions have a positive and significant effect. to company value.